Pemanfaatan Maggot Dalam Pengolahan Sampah Organik di Desa Wisata Bakas Kabupaten Klungkung - Putu Agus Prayogi; I Gusti Agung Sasih Gayatri; Egi Saputra; Yunda Angelika; Winda Frestika; Krisna Satria (Pubfine Media Group, 2024)
The Community Training and Mentoring Work Program is one of the main components of the Thematic KKN implemented by Group 6 in Bakas Village, Klungkung Regency, Bali. Through this program, the team provides training and mentoring to local communities in various fields, such as maggot cultivation, micro and small business development, and the use of information and communication technology to improve accessibility and promotion of tourism villages. The success of this program is reflected in the active participation of the community and the improvement of skills achieved. Recommendations were given to improve the sustainability of the program, through continuous evaluation and monitoring, as well as inclusion of education programs and environmental awareness in the development of tourism villages. Keywords: Training, Mentoring, Community, Maggot Farming, Micro and Small Enterprises, Information and Communication Technology, Tourism Village, Sustainability, Evaluation, Environmental Education.